The Twists and Turns of Diagnosis and Treatment of Pediatric Neuro-Behcet's Disease: A Case Report and Literature Review - Zhang, Qiao; Luo, Yizhen; Zhou, Jianli; Zhou, Shaoming; Wang, Zhaoxia (Frontiers in Pediatrics, 2021)
Background: The neurological manifestation of Behcet's disease (BD) is known as Neuro-Behcet's disease (NBD). The lack of a specific diagnostic method for NBD renders the diagnosis and treatment of NBD challenging. Methods and Results: We report a boy aged 11 years and 11 months who underwent right-eye intraocular lens implantation, appendectomy, perianal abscess removal, thalidomide therapy, and infliximab infusions for his Crohn disease. Magnetic resonance venography (MRV) and magnetic resonance imaging (MRI) were performed to address the onset of headache during the course of his treatment, and cerebral venous sinus thrombosis was detected. After the diagnosis of NBD, the patient was treated with anticoagulation therapy (nadroparin calcium), low-dose corticosteroids, and an immunosuppressant (cyclophosphamide), and consequently, he recovered. Conclusion: This case report shows that NBD is prone to misdiagnosis and missed diagnosis and should be diagnosed based on clinical manifestations and results from colonoscopy, pathological examination, and MRI or MRV.